MULTIFACETED CONSUMER BEHAVIOUR AND FACTORS INFLUENCING IN INLAND FISH CONSUMPTION IN ANAND DISTRICT, GUJARAT - PANIGRAHY, SHAKTI RANJAN; VAHONIYA, DILIP (Journal of the Inland Fisheries Society of India, 2021)
Anand district is number one in Inland fish production through ponds and tanks in Gujarat and increased cosmopolitan groups of population give a new thrust for Inland fish consumption in spite of poor show for this throughout Gujarat. Three hundred customers have been selected at the time of purchase in six major markets of Anand district looking into abundance presence of Inland fish at the market yards. Here consumer behaviour and consumption pattern of Inland fish consumption have been studied and data have been analysed through multiple regression, Garrett ranking technique and tabulation methods. Average monthly expenditure on consumption of Inland fish with respect to average food consumption was about 15%. About 80% of Inland fish purchase mainly carried out in the evening and about 94% of consumers consumed it at a time each purchase. Sunday was the preferred day and Surmai was the preferred fish for consumers and taste was the number one factor for attracting consumer to the market yard. Overall, though Surmai fish has been accepted in all the income categories but by increasing income preference for inland fish consumption is shifted more towards higher price segment. As Income increases percentagewise inland fish consumption decreases but at the same time quantity of fish consumption increases. Inland fish marketing is mainly relied on product, place and time of fish consumption. Key words: Inland fish consumption, Consumption pattern, Consumer Behaviour